2018
DOI: 10.13170/depik.7.3.11020
|View full text |Cite
|
Sign up to set email alerts
|

Akumulasi logam berat (Pb dan Cu) pada Akar dan daun mangrove Avicennia marina di Sungai Lamong, Jawa Timur

Abstract: Mangrove ecosystem of Lamong River is located in an area with dense human activities such as industrial, heavy traffic, settlements and harbour activities. These activities could triggered the input of heavy metals, especially Pb and Cu. Mangrove ecosystem can be developed as a control of heavy metal pollution and also as a pollutant trap. In this study, the analysis of heavy metals (Pb and Cu) in water, sediment and mangorve's roots and leaves were measured. The aim of this study was to determine the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Our data indicate that Indonesian children living in an urban area are at increased risk for BLLs above the actual acceptable limit [20]. The increasing number of industries in Indonesia has been associated with rising heavy metal pollution in several areas such as in Jakarta and Medan [21], [22], [23], [24]. Research conducted in the city of Medan and Yogyakarta found that there is an apparent link between the increases of the intensity of a motor vehicle with the air lead levels in these two cities [25].…”
Section: Introductionmentioning
confidence: 70%
“…Our data indicate that Indonesian children living in an urban area are at increased risk for BLLs above the actual acceptable limit [20]. The increasing number of industries in Indonesia has been associated with rising heavy metal pollution in several areas such as in Jakarta and Medan [21], [22], [23], [24]. Research conducted in the city of Medan and Yogyakarta found that there is an apparent link between the increases of the intensity of a motor vehicle with the air lead levels in these two cities [25].…”
Section: Introductionmentioning
confidence: 70%
“…Many studies have highlighted that an increase in pollution from heavy metals in water bodies that serve as the primary water sources for various fishery activities. Several areas in East Java have been the focus of research on water pollution, including; Lamongan (Sugiyanto, Yona and Kasitowati, 2016;Awaliyah, Yona and Pratiwi, 2018), Pasuruan (Salsabila, 2021;Purnomo, 2022), and Banyuwangi (Setyaningrum et al, 2018;Yona et al, 2018). The findings from these studies reveal the presence of various heavy metals in almost all coastal areas of East Java.…”
Section: Introductionmentioning
confidence: 94%
“…Dilihat dari letak geografis Sungai Banjir Kanal Timur yang ditetapkan sebagai lokasi penelitian merupakan bagian hilir, sehingga memungkinkan terjadinya akumulasi logam berat yang terbawa oleh arus sungai dari hulu. Menurut Awaliyah et al, (2018), konsentrasi logam berat Cu dan Pb pada air mengalami peningkatan konsentrasi seiring dengan semakin dekatnya dengan muara sungai. Logam berat yang larut dalam air akan terbawa sampai ke muara dan terakumulasi sehingga konsentrasinya relatif besar karena mudah terdistribusi.…”
Section: Parameter Cu Pb Bod Dan Cod Perairanunclassified